REALISTIC MATHEMATICS EDUCATION ON MATHEMATICS LEARNING OUTCOMES IN FRACTIONS MATERIALS OF CLASS III STUDENTS - yeyen Febrilia; Rahayu Condro Murti; Jarmi .; Asih Mardati; Julianto Saputra (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Indonesia student’s understanding of Mathematics is very low. This study aims to determine the positive effect of the Realistic Mathematical Education learning approach on the learning outcomes of grade III fractions at SD Negeri 2 Riau Silip. This research method is pre-experimental with one group pretest-posttest design. Population Data collection techniques use an instrument with a total of 5 questions, both pretest and posttest. Data were analyzed with descriptive statistics and inferential analysis with the help of the SPSS 23 program on prerequisite tests and hypothesis tests. The results of the study stated that the results of the descriptive analysis showed an increase in the average score of students' learning outcomes was 40.72 to 72.55. In addition, the results of the inferential analysis showed a significance value of 0.001 <0.05 so H0 was rejected and Ha was accepted. This states that RME has a positive influence on the learning outcomes of class III students at SD Negeri 2 Riau Silip.